PrP Expression and Replication by Schwann Cells: Implications in Prion Spreading - Follet, Jérôme (American Society for Microbiology, 2002)
Prion infection relies on a continuous chain of PrP(c)-expressing tissues to spread from peripheral sites to the central nervous system (CNS). Direct neuroinvasion via peripheral nerves has long been considered likely. However, the speed of axonal flow is incompatible with the lengthy delay prior to the detection of PrP(Sc) in the brain. We hypothesized that Schwann cells could be the candidate implicated in this mechanism; for that, it has to express PrP(c) and to allow PrP(Sc) conversion. We investigated in vivo localization of PrP(c) in sciatic nerve samples from different strains of mice. We demonstrated that PrP(c) is mainly localized at the cell membrane of the Schwann cell. We also studied in vitro expression of PrP(c) in the Schwann cell line MSC-80 and demonstrated that it expresses PrP(c) at the same location. More specifically, we demonstrated that this glial cell line, when infected in vitro with the mouse Chandler prion strain, both produces the PrP(Sc) till after 18 passages and is able to transmit disease to mice, which then develop the typical signs of prion diseases. It is the first time that infection and replication of PrP(Sc) are shown in a peripheral glial cell line.